Web-based portable network traffic monitoring system based on embedded linux and SBC - Md. Mostafijur, Rahman; Zahereel Ishwar, Abdul Khalib; R. Badlishah, Ahmad, Prof. Madya Dr.; Salina, Mohd Asi (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/